Des reines violentes - Damien Bril (Les Cahiers de l'École du Louvre)
In 17th-century France, the warlike dimension of violence became one of the fundamental iconographic attributes of royalty. Although at the outset they were excluded from managing affairs of state on account of Salic law, the queens Marie de’ Medici and Anne of Austria nonetheless sought to wear the costume of the chief of command in their portraits, in particular when they were placed at the head of the government in the position of regent. To achieve this, however, they did not employ a single formula but each developed personal strategies that varied in their means, objectives and results, borrowing in turn from mythological portraiture and historical representation to define their role in the management of conflicts, and ultimately of royal power.